Natural-based food packaging from banana leaves: Innovation toward sustainable and circular food systems - Ajeng Putri Ardiani (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Global food waste and the extensive use of non-biodegradable plastics in food packaging remain among the most pressing environmental challenges, contributing to greenhouse gas emissions, resource depletion, and economic losses. In response, bio-based and biodegradable materials derived from agricultural residues have gained attention as sustainable alternatives. Among these, banana leaves offer great potential due to their abundance, biodegradability, and mechanical strength. This study was conducted to synthesize current advancements, challenges, and future directions in the development of banana-leaf-based materials for sustainable food packaging applications, with particular attention to food protection and quality preservation. Methods: This study employs a systematic literature review that integrates material, environmental, and policy perspectives to evaluate the feasibility, performance, and sustainability of banana-leaf-based food packaging. Findings: Technological advancements such as enzymatic pulping, nanocellulose extraction, and hybrid biopolymer formation have enhanced the mechanical, thermal, and biodegradation properties of banana-leaf composites, while also improving barrier and antimicrobial functionalities relevant to food safety and shelf-life extension. Life cycle assessments show reduced energy use and emissions compared to plastic packaging, while socioeconomic analyses highlight benefits for rural livelihoods. Policy reviews emphasize the need for regulatory harmonization to accelerate industrial adoption. Conclusion: Banana-leaf-based materials demonstrate strong potential as eco-friendly food packaging that not only aligns environmental, social, and economic sustainability goals, but also supports food safety, reduces spoilage, and contributes to food quality preservation when supported by technological innovation and coherent policy frameworks. Novelty/Originality of this article: This study presents an integrated synthesis of material performance, food safety relevance, environmental assessment, and policy implications, positioning banana-leaf packaging as a viable and scalable approach toward sustainable food systems and circular economy transitions.